Diagnostics of chronic small intestinal obstruction in patient with ectopic pancreas in the Meckel's diverticulum (case report) - Zinaida A. Lemeshko; O. S. Shifrin; A. V. Korolev; T. L. Lemina; I. A. Sokolina; A. Ye. Leonovich; K. A. Lesko; A. S. Tertychny; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2016)
Aim of the case report presentation. To draw attention of general practitioners to the rare case of intestinal obstruction - intussusception of Meckel's diverticulum in small intestinal lumen. Key points. The present case is characterized by development of chronic small-intestinal obstruction due to repeating intussusception of Meckel's diverticulum in the small intestinal lumen. Episodes of intussusception manifested clinically by attacks of severe right iliac pain that made patient to take «embryonic posture». Deep palpation revealed «spastic bowel» sign in the area of intussusception. A specific type of intussusception was detected by transabdominal ultrasound: thickening and «lamination of intestinal wall» due to «diverticulum interposition» into the lumen of ileum and «overlaying» of wall layers. The evacuation delay at the small intestine was followed by dilation of overlying loops of the small intestine containing bulky liquid content; pendular movement of liquid observed at ultrasonography with visible «air-fluid levels» at plain radiograph. The patient at the same time had frequent liquid stool that indicated presence of incomplete obstruction. Surgical intervention for intussusception and resection of diverticulum-containing portion of the small intestine resulted in improvement of the patient state, relief of pain attacks and signs of intestinal obstruction. Histological examination of resected specimen revealed the presence of ectopic pancreatic tissue in the Meckel's diverticulum wall. Conclusion. Carrying out differential diagnosis in colicky abdominal pain should encompass existence of Meckel's diverticulum with recurrent small intestinal intussusception that can result in chronic intestinal obstruction. In diverticulum wall ectopic pancreas can be detected. Key words: ileus, Meckel's diverticulum, ectopic pancreas.